Analisis Hasil Belajar Siswa melalui Pelaksanaan Pembelajaran Daring pada Mata Pelajaran Ekonomi - Ummi Kalsum; Ade Irma Suryani; Eko Prasetiyo (Departement of Mathematics Education, 2023)
The purpose of this study was to find out student learning outcomes through online learning in economics subjects at SMA N 05 Bengkulu Utara. This type of research is a quantitative descriptive research. The population in this study were 58 students of SMA N 05 North Bengkulu Class 12 IPS Regular who were still active. The sample used is Random Sampling. Data collection techniques use observation, questionnaires and documentation. Data Analysis Techniques use the Average Formula. The results of this study show that: Student completeness in economics subjects at SMA N 05 Bengkulu Utara for the 2021/2022 academic year that out of 5 classes, namely class XII IPS 1, XII IPS 2, XII IPS 3, XII IPS 4, XII IPS 5 with the results of learning by students in Economics at SMA N 05 North Bengkulu into the Good category with a percentage score of 69% and an average score of 77.89. This can be seen from the learning outcomes assessment criteria located in the interval (62-81). And also Online Learning for class XII IPS 1, XII IPS 2, XII IPS 3, XII IPS 4, XII IPS 5 in Economics Subjects at SMA N 05 North Bengkulu belongs to the Good category with a percentage value of 100% entering the Very Good category located at intervals (63-80). From all the data that has been obtained, it can be seen that the average score obtained by these students is in the Good category in taking lessons seriously.